MEASUREMENT OF ECONOMIC EFFICIENCY OF UPLAND RICE FARMING IN DIFFERENT LAND OWNERSHIP STATUS IN MAUSAMBI VILLAGE, MAUROLE SUB-DISTRICT, ENDE REGENCY - Lanamana, Willybrordus (Jurnal AGRISEP, 2019)
This research is to: (1) analyze the level of economic efficiency of upland rice farming in different land ownership status and (2) analyze the factors that influence the economic efficiency of upland rice farming in different land ownership status. The data analysis method used was the production function approach and stochastic frontier cost function. The analysis results show that seed and fertilizer price variables have a significant impact on the 99% significance level and are positive. Labor wage has no significant impact on production costs and is negative. Production variable has a significant impact on the 99% significance level. Landowner and farmhand dummy variables have a 99% significant level and are positive. It can be interpreted that the production costs in both the landowner and farmhand land ownership status are higher than in the pawn taker land ownership status. The average level of economic efficiency of the landowner is higher than the farmhand and pawn taker ownership status. Factors that influence the economic efficiency of upland rice farming include: age, duration of farming, frequency of obtaining information, membership of farmer groups, other sources of income, landowner dummy and farmhand dummy.